Using near-infrared reflectance spectroscopy for rapid nutrient evaluation of sorghum silage - K.J. Budiongo; L.H. Harbers; B.W. Seabourn; K.K. Bolsen; B.E. Brent (Kansas Agricultural Experiment Station Research Reports, 1996)
This research was designed to develop a set of prediction equations to measure nutrient composition of Kansas sorghum silages by near-infrared reflectance spectroscopy (NIRS). Because sorghum silages are highly variable in grain content, we included a large number of cultivars to develop a robust set of equations for dry matter, crude protein, neutral detergent fiber, and acid detergent fiber. The results indicate that NIRS analysis of sorghum silages is feasible.
Keywords: Cattlemen& #x27; s Day; 1996; Kansas Agricultural Experiment Station contribution; no. 96-334-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 756; Beef; Sorghum silage; Nutrient evaluation; Near-infrared reflectance spectroscopy